2022
DOI: 10.1177/23259671221094799
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Status With Treatment Delays for Pediatric and Adolescent Patients Undergoing Surgery for Patellar Instability

Abstract: Background: Health care disparities have been highlighted in pediatric sports medicine, but the association between insurance status and delayed care for patients undergoing surgery for patellar instability has not been defined. Purpose: To determine whether there is an association between insurance status and delays in care in pediatric and adolescent patients undergoing surgery for patellar instability. Study Design: Cohort study; Level of evidence, 3. Methods: This was a retrospective case series at a safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The included research articles were classified into five mutually exclusive primary focus areas during the data extraction phase: (1) access to and participation in sports , (2) access to SEM care , (3) health-related outcomes in SEM , (4) study methodology and (5) provider representation in SEM (table 1, online supplemental table S4). Most included studies were related to access to and participation in sports (n=45, 44%),17–61 followed by access to SEM care (n=28, 27%),62–89 health-related outcomes in SEM (n=24, 23%),90–113 provider representation in SEM (n=5, 5%)114–118 and methodology (n=1, 1%) 119…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included research articles were classified into five mutually exclusive primary focus areas during the data extraction phase: (1) access to and participation in sports , (2) access to SEM care , (3) health-related outcomes in SEM , (4) study methodology and (5) provider representation in SEM (table 1, online supplemental table S4). Most included studies were related to access to and participation in sports (n=45, 44%),17–61 followed by access to SEM care (n=28, 27%),62–89 health-related outcomes in SEM (n=24, 23%),90–113 provider representation in SEM (n=5, 5%)114–118 and methodology (n=1, 1%) 119…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the various combinations of potential causes of health disparities that were assessed and the number of articles that addressed these combinations. The combination of race/ethnicity and sex was the largest combination, with 13 articles looking at both characteristics (and in some cases additional characteristics) in relation to health disparities 21 32 35 62 95 97 103 105 107 108 115 116 118…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of patellar instability and operative treatment with MPFLR, certain socioeconomic characteristics may be of benefit or an obstacle to early recognition of patellar instability and seeking appropriate treatment for the condition. Prior analyses by Li et al and Allahabadi et al have found that race and insurance status may be significant predictors of access to surgical care, timing of initial evaluation and surgery, and cost of treatment among patellar instability patients [ 1 , 16 ]. This is especially important given that chronicity of instability symptoms has been associated with increased likelihood of sequelae such as chondral lesions, chronic pain, and early osteoarthrosis [ 5 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are subject to the implicit and explicit biases of the patients and athletes we take care of every day based on the color of our skin. We take issues of diversity, equity, and inclusion very seriously, not only from an academic standpoint 1 , 2 , 5 , 6 , 8 , 10 , 11 , 14 16 but also from a personal standpoint. Patients view us, however, through the color of our skin, making assumptions about us regardless of how we self-report/self-identify.…”
mentioning
confidence: 99%